Етнофестивалі другої половини ХХ – початку ХХІ століття як складова фольклорної культури Болгарії - Огієнко, І. (Матеріали до української етнології, 2021)
Статтю присвячено дослідженню фольклорної фестивальної культури в Болгарії в другій половині ХХ – на початку ХХІ ст. Розглянуто характерні особливості фольклорної фестивальної культури Болгарії, визначено основні функції фольклорних фестивалів, класифіковано низку відомих міжнародних, національних і локальних фестивалів етнофольклорного напряму, що відбуваються в різних містах і селах Болгарії. Описано перші етнофестивалі в Болгарії, такі як Собор народної творчості і тваринництва в Рожені, Собор народної творчості в Копривщиці, Міжнародний фольклорний фестиваль у Бургасі, Собори народної творчості «Пірін співає», «Балкан співає і розповідає» та ін., які проводяться з початку 60‑х років ХХ ст. до сьогодні й саме з яких розпочався розвиток фольклорно-фестивального руху в Болгарії. The article is dedicated to the study of folklore festival culture in Bulgaria in the mid to late 20th – early 21st century. The characteristic features of the folklore festival culture of Bulgaria are considered, the main functions of the folklore festivals are determined, and a number of well-known international, national, and local ethnic folklore festivals taking place in different cities and villages of Bulgaria are classified. The first ethnofestivals in Bulgaria are described, such as the Festival of Folk Art and Animal Husbandry in Rozhen, the Festival of Folk Art in Koprivshtitsa, the International Folklore Festival in Burgas, the Festivals of Folk Art Pirin Sings, Balkan Sings and Tells, which have been held from the 1960s till nowadays. They have started the development of the folklore festival movement in Bulgaria.